Time-Qualified Patterns of Variation of PPARγ, DNMT1, and DNMT3B Expression in Pancreatic Cancer Cell Lines - Valerio Pazienza; Francesca Tavano; Massimo Francavilla; Andrea Fontana; Fabio Pellegrini; Giorgia Benegiamo; Vincenzo Corbo; Fabio Francesco di Mola; Pierluigi Di Sebastiano; Angelo Andriulli; Gianluigi Mazzoccoli (PPAR Research)
Carcinogenesis is related to the loss of homeostatic control of cellular processes regulated by transcriptional circuits and epigenetic mechanisms. Among these, the activities of peroxisome proliferator-activated receptors (PPARs) and DNA methyltransferases (DNMTs) are crucial and intertwined. PPARγ is a key regulator of cell fate, linking nutrient sensing to transcription processes, and its expression oscillates with circadian rhythmicity. Aim of our study was to assess the periodicity of PPARγ and DNMTs in pancreatic cancer (PC). We investigated the time-related patterns of PPARG, DNMT1, and DNMT3B expression monitoring their mRNA levels by qRT-PCR at different time points over a 28-hour span in BxPC-3, CFPAC-1, PANC-1, and MIAPaCa-2 PC cells after synchronization with serum shock. PPARG and DNMT1 expression in PANC-1 cells and PPARG expression in MIAPaCa-2 cells were characterized by a 24 h period oscillation, and a borderline significant rhythm was observed for the PPARG, DNMT1, and DNMT3B expression profiles in the other cell lines. The time-qualified profiles of gene expression showed different shapes and phase relationships in the PC cell lines examined. In conclusion, PPARG and DNMTs expression is characterized by different time-qualified patterns in cell lines derived from human PC, and this heterogeneity could influence cell phenotype and human disease behaviour.